2020
DOI: 10.1016/j.jaci.2019.12.899
|View full text |Cite
|
Sign up to set email alerts
|

How does parental history of atopic disease predict the risk of atopic dermatitis in a child? A systematic review and meta-analysis

Abstract: Background: Parental history of atopic disease is a wellestablished risk factor for the development of atopic dermatitis (AD), but several aspects of this association remain unclear. Objective: We sought to determine the association of parental history of atopic disease with AD in offspring. Methods: We searched PubMed and EMBASE through June 2018 for relevant records and adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Pooled odds ratios (ORs) with 95% CI were calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 248 publications
(197 reference statements)
4
41
1
3
Order By: Relevance
“…Together with our study findings, maternal inflammation, 24 maternal microbiome, 25 parental history of atopic disease, 26 It was already shown that maternal IgG and allergens can cross through the placenta, influencing the child's immune system. 22,23 Yet, the linkage between cord blood levels of maternal immunoglobulins to child's atopy and allergy remains unclear.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Together with our study findings, maternal inflammation, 24 maternal microbiome, 25 parental history of atopic disease, 26 It was already shown that maternal IgG and allergens can cross through the placenta, influencing the child's immune system. 22,23 Yet, the linkage between cord blood levels of maternal immunoglobulins to child's atopy and allergy remains unclear.…”
Section: Discussionsupporting
confidence: 85%
“…During pregnancy, the maturation of the embryonal immune system can be altered by different maternal conditions and exposures, which results in allergic or other immunological diseases later in life. Together with our study findings, maternal inflammation, 24 maternal microbiome, 25 parental history of atopic disease, 26 and maternal diet during pregnancy 27 have all been associated with childhood allergic dermatological conditions such as eczema and atopic dermatitis. As drug allergy has been shown to be associated with immunological intolerance, maternal known drug allergy may affect the developing fetal immune system, resulting in dermatological and allergic morbidity later during childhood.…”
Section: Discussionsupporting
confidence: 84%
“…1 Nutrition, pollution, microbiome, and other environmental factors that interact with the genetic background can reshape the fetal genetics and epigenetics. 2,3 These genetic and epigenetic factors can leave long-term in uences on a patient's immunological, cardiovascular, and other systemic functioning and can lead to diseases later in life. 4,5 Many birth cohort studies have investigated the link between perinatal exposure and the outcomes of atopic diseases in an attempt to identify possible predictive biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…AD causes health-related burdens associated with pruritus and poor quality of life [1]. A systematic review and meta-analysis showed that parental history of AD increased the risk of AD in the offspring (pooled odds ratio: 3.30, 95% con dence interval [CI]: 2.45-4.42) [2]. Genetically susceptible individuals of AD have a higher risk of AD.…”
Section: Introductionmentioning
confidence: 99%